Quantification of potassium levels in cells treated with Bordetella adenylate cyclase toxin - Wald, Tomas; Petry-Podgorska, Inga; Fiser, Radovan; Matousek, Tomas; Dedina, Jiri; Osicka, Radim; Sebo, Peter; Masin, Jiri (Analytical biochemistry, 2014)
The aim of this study was to compare two methods for quantification of changes in intracellular potassium concentration (decrease from ∼140 to ∼20mM) due to the action of a pore-forming toxin, the adenylate cyclase toxin (CyaA) from the pathogenic bacterium Bordetella pertussis. CyaA was incubated with stably transfected K1 Chinese hamster ovary cells expressing the toxin receptor CD11b/CD18 and the decrease in potassium concentration in the cells was followed by inductively coupled plasma mass spectrometry (ICP-MS). It is shown that this method is superior in terms of sensitivity, accuracy, and temporal resolution over the method employing the potassium-binding benzofuran isophthalate-acetoxymethyl ester fluorescent indicator. The ICP-MS procedure was found to be a reliable and straightforward analytical approach enabling kinetic studies of CyaA action at physiologically relevant toxin concentrations (<1000ng/ml) in biological microsamples.
Keywords: RTX; draslík; antigeny CD18; lidé; CD11b Antigen; Mass Spectrometry; CD18 Antigens; Cricetinae; Adenylate Cyclase Toxin; intracelulární prostor; transfekce; CHO buňky; Humans; Cricetulus; Intracellular Space; fluorescenční barviva; CHO Cells; Fluorescent Dyes; Potassium; Bordetella pertussis; křečci praví; Adenylate cyclase toxin; zvířata; PBFI–AM; ICP–MS; adenylátcyklasový toxin; Animals; hmotnostní spektrometrie; Transfection; antigeny CD11b